Gardening-cooking based intervention for improving healthy eating habits in preschool children - Herawati, Herni Dwi; Kurniasari, Yulinda; Rahayu, Herwinda Kusuma; Hositanisita, Hastrin; Afifah, Effatul; Isvianti, Anggita; Susilowati, Novaeni Sri; Batubara, Saimarrasoki; Sonia, Putri (Paediatrica Indonesiana, 2024)
Background Preschool children generally have inadequate fruit and vegetable intake, but a high intake of calories. Nutrition education taught from an early age might instill good eating habits and behavior, especially regarding fruit and vegetable consumption. Objectives To compare preschoolers’ fruit and vegetable preferences, fiber intake, and consumption of high-calorie food before and after a gardening-cooking intervention. Methods This study had a quasi-experimental, pre- and post-test design, as well as intervention and control groups. Subjects were preschool children aged 4-6, selected by purposive sampling, with 33 subjects in each group. The intervention group engaged in nutrition education, gardening, and cooking programs. While the control group was not given the programs, only given nutrition education at the end of data collection. Data were analyzed using independent T-test, paired T-Test, Wilcoxon, and Mann-Whitney tests. Results There were significant increases in attitude score, fruit and vegetable preference, and fiber intake, as well as decreased intake of high calorie foods (P<0.05 for all) before and after treatment in the intervention group. In contrast, there were no significant changes in the control group pre- and post-test. Conclusion Gardening-cooking based intervention for 9 sessions is effective in improving attitudes, fruit and vegetable preferences, and fiber intake, as well as reducing high-calorie food consumption in preschool children.